La memoria de la muerte en “Viaje a la semilla” (Dossier: Muertos que narran) - Hwangpo, Mihyang Cecilia (2024)
In “Viaje a la semilla”, Alejo Carpentier endeavors to show, in various ways, what life, or death, means, on a personal and national level. This paper aims to study and explore death as incessant and polysemic, through the house, a private-public space, where subjects from various times and spaces coexist. At the same time, in order to understand this death, it is essential to analyze time, which cannot do without memory, since the past and the present coexist in memory. This memory (re) constructs life and death, and takes a step towards understanding what death means and represents.